Hersz, (Herszko, Henryk) Blumsztejn (1919 –?), wywiadowca Sekcji IV PUBP Siedlce, kierownik Sekcji II PUBP w Oławie na Dolnym Śląsku - CHARCZUK, Wiesław (Historia i Świat, 2012)
Siedlce district offi ce of public safety in lats in to 1944-1945. It take possession by staff of jewish origin 20%. They occupied positions of chiefs or they were employed in character of scout of section, who dealt with liquidation of independence underground. There was one of employee offi cer to from murders dating PUBP Hersz Blumsztejn, who has been employed as scout in section IV. By poles from hands rid nazi, now they have stood in one range with communist for battle with independence underground. There was among they Hersz Blumsztejn, surname is mentioned which who as responsible officer for quota in crime of killing without judicial sentence by local apparatus of safety in Siedlce, at least in night from 12 on 13 april 1945 16 persons. Then henry has been rescheduled as chief of section after loud crime to for service in structures of communist apparatuses of safeties for Kielce for on bottom Silesia II Siedlce Hersz Blumsztejn Oława. It worked in structures of apparatuses of safeties for january 1946 Hersz Blumsztejn.